What is the best indicator of the harmful use of alcohol? A narrative review. (6th April 2020) - Rehm, Jürgen; Crépault, Jean‐François; Wettlaufer, Ashley; Manthey, Jakob; Shield, Kevin
Abstract: Issues: The monitoring of the harmful use of alcohol is a key focus of global health efforts, including the Sustainable Development Goals. The current indicator of harmful alcohol use for Sustainable Development Goals is the national adult (15+ years) alcohol per capita consumption (APC) in litres of pure alcohol. Recently, the age‐standardised prevalence of heavy episodic drinking (HED) has been advanced as an alternative indicator. Approach: This narrative review is composed of a review of advantages and disadvantages of both indicators and an empirical analysis of their associations with alcohol‐attributable health harm. Key findings: APC is greatly associated with harm and is available for almost all countries on a yearly basis as it is largely derived from routinely collected statistics. HED is based on responses to population surveys not routinely performed for most countries. These surveys commonly exclude heavy drinking populations (e.g. army personnel, institutionalised, homeless). Even when included within the sampling frame, heavy drinkers are less likely to participate than other groups. The questions used to measure HED are susceptible to biases due to issues with respondents' comprehension, recall and misreporting. Furthermore, in a regression analysis of 182 countries, APC was better at predicting alcohol‐attributable harm than HED. APC was also correlated with changes in the alcohol‐attributable burden of disease (from 2010 to 2016), while HED was not. Implications: Based on these factors, APC was found to be the preferred indicator. Conclusions: APC should be retained as the main indicator of the harmful use of alcohol.